Sosialisasi Parenting: Pentingnya Digital Parenting untuk Mendidik Anak di Era Digital - Idrus, Muhammad Ainun; Ahmad, Andi; Pasalli, Hastria; Andini, Andini; Misraeni, Misraeni; Zahra, Fatimatus; Witri, Witri; Audy, Audy; Taufiq, Taufiq; Herdiana, Besse (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2025)
ABSTRACTThis discussion or outreach aims to educate the public about the importance of taking action or implementing rules and monitoring the use of technology. Digital parenting is a way to care for children in the digital or technological era. The method for implementing parenting outreach with the theme "Intergenerational Discussion: The Importance of Digital Parenting for Educating Children in the Digital Era" consists of presentation material (generational division, technological developments, and digital parenting), then followed by a question and answer discussion session. The number of participants who attended this activity was 46 people with a total of 26 people being sampled to fill out a questionnaire related to parenting socialization. The questionnaire contains 9 questions about pareting.Keywords: Parenting Socialization, Digital Parenting, digital era ABSTRAKDiskusi atau sosialisasi ini bertujuan untuk mengedukasi masyarakat pentingnya melakukan pembatasan atau menerapkan aturan serta pengawasan terhadap penggunaan teknologi. Digital parenting merupakan cara untuk mengasuh anak ditengah era digital atau teknologi. Metode pelaksanaan sosialisasi parenting dengan tema “Diskusi Lintas Generasi : Pentingnya Digital Parenting Untuk Mendidik Anak di Era Digital” terdiri atas pemaparan materi (Pembagian generasi, perkembangan teknologi, dan digital parenting), kemudian dilanjutkan dengan sesi diskusi tanya jawab. Jumlah peserta yang hadir dalam kegiatan ini berjumlah 46 orang dengan total 26 orang yang dijadikan sebagai sampel untuk mengisi angket terkait sosialisasi parenting. Angket berisikan 9 pertanyaan seputar pareting.Kata Kunci: Sosialisasi Parenting, Digital Parenting, era digital